2011
DOI: 10.1055/s-0031-1275520
|View full text |Cite
|
Sign up to set email alerts
|

The Early Origins of Cardiovascular Health and Disease: Who, When, and How

Abstract: Almost 30 years ago, a series of epidemiological studies popularized the early programming theory that had resulted from observed associations between low birthweight and increased cardiovascular morbidity and mortality later in life. Since then, several clinical and experimental models have been created to understand the principles and mechanisms of this fascinating phenomenon and describe its relevance to the pathophysiology of cardiovascular and many other chronic diseases. Despite the growing body of publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 137 publications
1
38
0
Order By: Relevance
“…Of note, multigenerational highaltitude populations demonstrate protection against the effects of high-altitude hypoxia on fetal growth (14)(15)(16)(17)(18). Experimental studies in animal models support the likelihood that prenatal hypoxia can program cardiac, vascular, and metabolic dysfunction in the adult offspring (19)(20)(21), and that high-altitude ancestry protects against the effect of chronic hypoxic development on fetal growth (22).…”
mentioning
confidence: 99%
“…Of note, multigenerational highaltitude populations demonstrate protection against the effects of high-altitude hypoxia on fetal growth (14)(15)(16)(17)(18). Experimental studies in animal models support the likelihood that prenatal hypoxia can program cardiac, vascular, and metabolic dysfunction in the adult offspring (19)(20)(21), and that high-altitude ancestry protects against the effect of chronic hypoxic development on fetal growth (22).…”
mentioning
confidence: 99%
“…Numerous epidemiological and animal studies have shown that stressors such as hypoxia can influence the growth and developmental trajectories of the fetus, thereby increasing its susceptibility to long-term health complications, including cardiovascular diseases (reviewed in Rueda-Clausen et al 1 ). In support of this, we and others have shown that prenatal hypoxia is associated with long-term alterations in vascular function, characterized by reduced NO-mediated vasodilation, as well as increased responsiveness to adrenergic vasoconstrictors.…”
mentioning
confidence: 99%
“…Based on observational surveys, the risk factors of CVD are rapidly increasing, both in Iranian adults [2] and adolescents [7]. A growing body of evidence suggests that CVD is affected by exposure factors in early life [8][9][10]. Human milk feeding is an important factor that has been associated with reduced CVD risks [11,12].…”
mentioning
confidence: 99%